EFEKTVITAS KEGIATAN TELAAH STAF SEBAGAI BAHAN PERTIMBANGAN KEBIJAKAN DI BP2D PROVINSI JAWA BARAT TAHUN 2025 - Muhammad Hassan Ma'muur; Novie Indrawati Sagita; Agus Taryana (LPPM Universitas Abdurrab, 2026)
This study examines the effectiveness of the implementation of Staff Review Activities as a forum supporting policy deliberation within the Regional Research and Development Agency of West Java Province. Ideally, Staff Review Activities are designed as an internal quality assurance mechanism to ensure the quality of policy analyses and recommendations prior to their use in decision-making processes. However, in practice, the implementation of these activities has not functioned optimally. This study aims to analyze the level of effectiveness of Staff Review Activities, identify factors influencing their implementation, and formulate strategies to enhance their effectiveness as input for policy deliberation. The main argument of this study is that the effectiveness of Staff Review Activities is largely determined by procedural clarity, the quality of substantive discussion processes, and the continuity of follow-up mechanisms. This research employs a qualitative descriptive approach, with data collected through participatory observation, in-depth interviews with key informants, and documentation and literature review. The findings indicate that the implementation of Staff Review Activities has not yet been optimal, as reflected by the absence of standardized operational procedures, a tendency for the forum to shift toward administrative routines, weak documentation of review outcomes, and suboptimal follow-up mechanisms. These findings highlight the importance of strengthening procedural frameworks and organizational culture to enhance the quality of evidence-based policy recommendations within local government institutions.